Monitoramento de micro-organismos indicadores de higiene em linha de abate de bovinos de um matadouro-frigorífico habilitado à exportação no oeste do Paraná - Brandao, Juliana Luisa; Bueno do Prado Guirro, Erica Cristina; de Arruda Pinto, Paulo Sergio; Nero, Luis Augusto; Pinto, José Paes de Almeida Nogueira [UNESP]; Bersot, Luciano dos Santos (Universidade Estadual de Londrina (UEL), 2012)
Indicators microorganisms can be used as a method for evaluating the sanitary quality of food products, indicating the suitability of conditions for obtaining, processing and storage of food. This study sought to evaluate surface contamination of cattle carcasses that come from a slaughter plant under Federal Inspection in western Parana by mesophilic bacteria (AM), Enterobacteriaceae (EB), coliform at 35 degrees C (TC) and E. coli (EC). Surface samples were collected from 25 carcasses, each at 4 different points of slaughter, for non-destructive method. The samples were diluted in decimal scale and incubated in Petrifilm (R) plates. Were found averages of 1.46; 0.3; 0.23 and 0.21 log CFU / cm (2) for AM, EB, CT and EC, respectively. The values to be found were well below those recommended by the decision 471/2001 of the European Union and several other authors surveyed, indicating the effectiveness of the hygienic process industry.
Monitoring of hygiene indicator microorganisms in a line of cattle slaughter in a slaughter plant enabled for export in western Parana
Keywords: Microorganisms; indicators; processing; contamination